The burden of generational harm due to alcohol use in Tanzania: A mixed method study of pregnant women. - Kirstin West; Alena Pauley; Mia Buono; Miriana Mikindo; Yvonne Sawe; Joseph Kilasara; Francis Sakita; Sharla Rent; Bariki Mchome; Blandina T Mmbaga; Catherine A Staton (PLOS Global Public Health)
Background Rates of prenatal alcohol use in Sub-Saharan Africa (SSA) are increasing despite regulatory bodies urging pregnant women to abstain from alcohol. Tanzania has minimal policies, interventions, and educational programs addressing prenatal alcohol exposure. Consequently, a considerable number of mothers and their fetuses are exposed to alcohol, leading to serious health consequences like fetal alcohol spectrum disorder (FASD). Our study aims to understand the alcohol use practices of pregnant women, the knowledge and attitudes related to prenatal alcohol exposure among different genders and generations, and how these may be influenced by community perceptions and cultural beliefs among patients at Kilimanjaro Christian Medical Center (KCMC). Methods A total of 676 individuals seeking care at the KCMC Emergency Department (ED) or Reproductive Health Center (RHC) met our inclusion criteria, were approached for participation using a systematic random sampling method, and were enrolled. Of those, 541 women and 114 men completed the survey. The quantitative analysis focused exclusively on survey data from 533 women who reported their pregnancy status and age. Descriptive frequencies were used to compare sociodemographic factors and alcohol use practices across three female groups stratified by pregnancy status and age. Nineteen survey participants-both men and women-were purposively selected for qualitative semi-structured in-depth interviews (IDIs) exploring knowledge, attitudes, and cultural beliefs surrounding alcohol use during pregnancy. A grounded theory approach was used to analyze IDIs in NVivo. Results A large percentage of pregnant women reported consuming alcohol at least once per week (42.2%). Older non-pregnant women exhibited the highest rate of alcohol use per week (66.0%). Many older non-pregnant women (28.7%) perceived alcohol use as acceptable during pregnancy. Younger non-pregnant women had the highest prevalence of harmful or hazardous drinking (HHD) at 16.4%. This group also reported the highest weekly alcohol expenses, with 18.1% spending over 10,000 Tanzanian shillings (TZS) per week. Median [IQR] DrInC scores were 0 [0-0] for pregnant women, 0 [0-7] for younger non-pregnant women, and 0 [0-1] for older non-pregnant women. Older non-pregnant women exhibited the highest prevalence of depression (31.4%). Median [IQR] PHQ-9 scores were 4 [3-6.25] for pregnant women, 5 [2-8] for younger non-pregnant women, and 6 [3-10] for older non-pregnant women. Qualitative analyses demonstrated that (1) cultural beliefs are intricately tied to perceived benefits of prenatal alcohol exposure, (2) a history of alcohol use preceding pregnancy largely influences prenatal alcohol use, and (3) community views of PWCA are negative. Conclusions Our findings demonstrate high rates of prenatal alcohol use in Moshi, Tanzania, with pre-pregnancy alcohol use as a significant predictor. Despite generally negative views of pregnant women who consume alcohol (PWCA), some sociocultural beliefs and limited knowledge about the dangers of prenatal alcohol exposure encouraged alcohol use during pregnancy. To improve health outcomes and reduce alcohol-related pregnancy complications for current and future generations, community-wide health messaging and pre-pregnancy interventions may prove beneficial for pregnant women and women of reproductive age who consume alcohol.